PENGEMBANGAN ALAT PERMAINAN EDUKATIF DALAM PEMBELAJARAN BAHASA ARAB DI MADRASAH IBTIDAIYAH WAHID HASYIM SLEMAN YOGYAKARTA (Universitas Negeri Semarang, 2018)
Learning Arabic needs to look for an ideal formulation, especially those relating to the use of media that areneeded now. The provision of supporting media for learning Arabic is still rare. The scarcity of such studiesrequires the writer to be interested in actually doing research on this. This study aims to produce an appropriateand appropriate Arabic language learning media for third grade students of Wahid Hasyim SlemanYogyakarta Madrasah Ibtidaiyah Yogyakarta seen from the results of the validation of media experts, materialexperts, and teacher and student responses to the educational game tools developed. The results showed that theassessment of media experts on the appropriateness of educational game equipment from the aspect of displaydesign with an average score of 4, 78 categories were very good and aspects of use with an average score of 5.0categories were very good. The assessment of material experts on the appropriateness of educational gameequipment from the aspect of content / material with an average score of 4.0 good categories and aspects oflearning with an average score of 4, 37 categories is very good. The results of the teacher's response to theappropriateness of educational game tools showed that the teacher gave a positive response from the aspect ofcontent / material with an average score of 3.86 in both categories, aspects of learning with an average score of4.06 good categories, aspects of use with average scores 4.08 good categories, and display aspects with anaverage score of 4.23 good categories. AbstrakPembelajaran bahasa Arab perlu dicarikan formulasi idealnya, terutama yang berkaitan denganpemanfaatan media yang sangat dibutuhkan saat ini. Penyediaan media pendukung pembelajaranbahasa Arab saat ini masih langka. Kelangkaan kajian demikian menuntut penulis tertarik untuksecara nyata melakukan penelitian tentang ini. Penelitian ini bertujuan untuk menghasilkan mediapembelajaran bahasa Arab yang sesuai dan layak untuk siswa kelas III Madrasah IbtidaiyahWahid Hasyim Sleman Yogyakarta dilihat dari hasil validasi ahli media, ahli materi, dan responguru serta siswa terhadap alat permainan edukatif yang dikembangkan. Hasil penelitianmenunjukkan bahwa penilaian ahli media terhadap kelayakan alat permainan edukatif dari aspekdesain tampilan dengan rata- rata skor 4, 78 kategori sangat baik dan aspek penggunaan denganrata- rata skor 5,0 kategori sangat baik. Penilaian ahli materi terhadap kelayakan alat permainanedukatif dari aspek isi/ materi dengan rata- rata skor 4,0 kategori baik dan aspek pembelajarandengan rata- rata skor 4, 37 kategori sangat baik. Hasil respon guru terhadap kelayakan alatpermainan edukatif menunjukkan bahwa guru memberikan respon positif dari aspek isi/ materidengan rata- rata skor 3,86 kategori baik, aspek pembelajaran dengan rata- rata skor 4,06 kategoribaik, aspek penggunaan dengan rata- rata skor 4,08 kategori baik, dan aspek tampilan dengan ratarataskor 4,23 kategori baik.